2016
DOI: 10.1179/2045772315y.0000000055
|View full text |Cite
|
Sign up to set email alerts
|

Medication-related problems in individuals with spinal cord injury in a primary care-based clinic

Abstract: Objective: To determine the frequency of medical problems, reason for referral/primary complaint, products used, medication-related problems, and polypharmacy in patients with spinal cord injury (SCI) seen at an interprofessional primary care mobility clinic. Design: Retrospective review of medical records of patients with SCI for patient visits between August 2012 and March 2013. Methods: Data were abstracted from medical records of patients with SCI. Results: Of 74 patients who presented to the clinic, 19 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…[6][7][8] As a result, treatment plans are often complex, 9,10 involving the concomitant use of multiple medications (i.e. polypharmacy), [11][12][13][14] which often include high-risk prescription drugs (e.g. opioids, benzodiazepines).…”
Section: Spinal Cord Injury and Dysfunction (Sci/d) Can Results In Permentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] As a result, treatment plans are often complex, 9,10 involving the concomitant use of multiple medications (i.e. polypharmacy), [11][12][13][14] which often include high-risk prescription drugs (e.g. opioids, benzodiazepines).…”
Section: Spinal Cord Injury and Dysfunction (Sci/d) Can Results In Permentioning
confidence: 99%
“…14,15 While research is limited, 16 rates of polypharmacy range from 31% to 87%. [12][13][14] Polypharmacy is commonly associated with adverse drug events, 13 reduced medication adherence, 17 increased healthcare costs, 18 and lower quality of life. 19 A recent retrospective study found that individuals with SCI/D and polypharmacy were at a greater risk of experiencing an adverse drug event compared to a non-SCI/D control population.…”
Section: Spinal Cord Injury and Dysfunction (Sci/d) Can Results In Permentioning
confidence: 99%
“…People with spinal cord injury or dysfunction (SCI/D) typically take multiple medications (also known as polypharmacy) to manage secondary health complications (e.g., spasticity, urinary tract infections, pressure sores, respiratory infections) and multimorbidity (e.g., heart disease and diabetes) [1][2][3][4][5][6]. The reported polypharmacy rates among persons with SCI/D vary between 31 to 87% [6][7][8][9]. Pharmacotherapeutic treatment plans for persons with SCI/D often include a combination of prescription and over-the-counter medications and natural health products.…”
Section: Introductionmentioning
confidence: 99%
“…While a small body of research identifies a high prevalence of polypharmacy among persons with SCI/D [6][7][8][9], there remains a lack of critical research to help understand the experiences of different healthcare and service providers with MTM for this population. Therefore, the main purpose of this study is to understand the experiences of healthcare and service providers with MTM for persons with SCI/D, as well as the barriers and enablers of optimal MTM.…”
Section: Introductionmentioning
confidence: 99%
“…These conditions are often managed pharmacologically, and individuals with SCI are frequently prescribed multiple medications. Recent research suggests individuals with SCI who use multiple prescribed medications are at higher risk for adverse drug events and medication errors [5,6]. It is important to understand how prescription medication use impacts health and longevity in this population.…”
Section: Introductionmentioning
confidence: 99%